Potentialities of Program Analysis of Probable Outcome in Patients with Acute Poisoning by Mushrooms - V. I. Cherniy; V. A. Stepanyuk (Общая реаниматология, 2006)
The authors have developed a method for predicting a probable outcome in patients with acute poisoning by mushrooms, by examining the data of routine laboratory studies and dynamic interphase tensiometry and rheometry of sera from patients. Sixty-eight patients with acute mushroom intoxication were followed up. According to the outcome of the disease, they were divided into two groups: A) survivors and B) (deceased). In the sera of the deceased, the time of T monolayer relaxation and the angle of L1 tensiogram slope were 2.5 greater and PN3-PN4 and L2/L1 were 6 and 3.7 times less, respectively, than those in the survivors. Based on these data, by using the discriminant analysis, the authors have derived a classification rule that permits prediction of the outcome of the disease with a high degree of probability, by examining the results of dynamic interphase tensiometry and the data of routine laboratory studies of blood samples from patients with acute poisoning by mushrooms. The derived rule is of high significance (p<0.05).